The Dimension of Metacognitive Knowledge Categorized HOTS in Indonesian Language Exercise Book for Junior High School Students - Rahmawati, Dian; Suhartono, Suhartono; Indarti, Titik (International Journal for Educational and Vocational Studies, 2020)
The aims of this study is to examine the matter of training with the achievement of metacognitive knowledge categorized by HOTS. The research data focuses on the training of the dimension of metacognitive knowledge of HOTS in the books of seventh, eighth, and ninth grade students published by the Ministry of Education and Culture. The data collection techniques used are documentation and field notes. The results showed that the dimension of metacognitive knowledge in junior high school students' books was the metacognitive subtype of self-knowledge. Metacognitive knowledge in seventh and ninth grader students is trained through literacy activities and identified as a sub-type of self-knowledge based on the object phrases that wants students to choose books based on their interests and usefulness. The book for eighth grade student’s metacognitive self-knowledge is trained through reflection on learning material that has been learned. The questions categorized HOTS in eighth grade are marked with question words and verbs, and ninth grade are marked with question words. A slight difference is seen in seventh grade which is marked with nouns in the format of assignments in the form of tables.